Familial pneumothorax: towards precision medicine. Issue 3 (28th December 2017) - Scott, Rachel M; Henske, Elizabeth P; Raby, Benjamin; Boone, Philip M; Rusk, Rosemary A; Marciniak, Stefan J
Abstract : One in 10 patients suffering from primary spontaneous pneumothoraces has a family history of the disorder. Such familial pneumothoraces can occur in isolation, but can also be the presentation of serious genetic disorders with life-threatening vascular or cancerous complications. As the pneumothorax frequently precedes the more dangerous complications by many years, it provides an opportunity to intervene in a focused manner, permitting the practice of precision medicine. In this review, we will discuss the clinical manifestations and underlying biology of the genetic causes of familial pneumothorax.